Human Coronavirus 229E Infection Inactivates Pyroptosis Executioner Gasdermin D but Ultimately Leads to Lytic Cell Death Partly Mediated by Gasdermin E - Bowie, Andrew (My University, 2024)
Human coronavirus 229E (HCoV-229E) is associated with upper respiratory tract infections and generally causes mild respiratory symptoms. HCoV-229E infection can cause cell death, but the molecular pathways that lead to virus-induced cell death as well as the interplay between viral proteins and cellular cell death effectors remain poorly characterized for HCoV-229E. Studying how HCoV-229E and other common cold coronaviruses interact with and affect cell death pathways may help to understand its pathogenesis and compare it to that of highly pathogenic coronaviruses. Here, we report that the main protease (Mpro) of HCoV-229E can cleave gasdermin D (GSDMD) at two different sites (Q29 and Q193) within its active N-terminal domain to generate fragments that are now unable to cause pyroptosis, a form of lytic cell death normally executed by this protein. Despite GSDMD cleavage by HCoV-229E Mpro, we show that HCoV-229E infection still leads to lytic cell death. We demonstrate that during virus infection caspase-3 cleaves and activates gasdermin E (GSDME), another key executioner of pyroptosis. Accordingly, GSDME knockout cells show a significant decrease in lytic cell death upon virus infection. Finally, we show that HCoV-229E infection leads to increased lytic cell death levels in cells expressing a GSDMD mutant uncleavable by Mpro (GSDMD Q29A+Q193A). We conclude that GSDMD is inactivated by Mpro during HCoV-229E infection, preventing GSDMD-mediated cell death, and point to the caspase-3/GSDME axis as an important player in the execution of virus-induced cell death. In the context of similar reported findings for highly pathogenic coronaviruses, our results suggest that these mechanisms do not contribute to differences in pathogenicity among coronaviruses. Nonetheless, understanding the interactions of common cold-associated coronaviruses and their proteins with the programmed cell death machineries may lead to new clues for coronavirus control strategies.
PUBLISHED
cited By 0
Keywords: HCoV-229E; 3C-like protease; main protease; Mpro; virus-induced cell death; virus-induced pyroptosis; caspase-3; GSDMD; GSDME